ESG Adoption and Financial Performance: A Comparative Analysis of Listed Companies in Emerging Markets - Soegiharto (Business and Entrepreneurial Review, 2025)
This study investigates the relationship between Environmental, Social, and Governance (ESG) practices and financial performance among publicly traded companies in an emerging market context. Using a comprehensive dataset of the complete universe of 85 Indonesian listed companies with formal ESG assessments from 2021-2023, we examine how ESG adoption influences financial metrics while controlling for firm-specific characteristics. Our analysis employs a matched sample design comparing these 85 ESG- adopting firms with 170 carefully selected non-ESG counterparts to isolate the impact of sustainability practices. Results from panel data regression with fixed effects reveal that ESG adoption significantly enhances return on equity (ROE) by 2.76 percentage points and return on assets (ROA) by 1.54 percentage points. Among ESG firms, lower ESG risk scores correlate with superior performance, with negligible low- risk firms (combined) outperforming severe-risk firms by 6.03 percentage points in ROE. The relationship is moderated by firm size and financial leverage, with larger, less leveraged firms capturing greater ESG benefits. These findings support the business case for sustainability in emerging markets where ESG adoption remains limited (approximately 11% of listed companies), suggesting early adopters capture significant performance premiums